Pengaruh Kerapatan Akasia (Acacia nilotica) (L.) Willd. ex. Del. Terhadap Komposisi dan Keanekaragaman Tumbuhan Bawah di Taman Nasional Baluran Jawa Timur - Djufri, Djufri (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2011)
The research was done in Baluran National Park, Banyuwangi East Java. The objectives of this research were:  to determine of species composition, importance value of species, diversity index and evenness index, similarity index, distribution pattern of species, and species association. This research used the quadrat method. The determination of the species distribution was calculated using Poisson distribution formula and the determination of association was calculated using contingency table. The results of this research indicated that,  there were 61 species of  plant belong to20 familiy. The importance value was between 0,97-55,65%, and species with high importance value is Brachiaria reptans, Thespesia lanpas, Dichantium coricosum, and Oplismenus burmanii. The diversity index was between 2,0851-3,4033, and evenness index was between 1,7199-1,9984. The distribution pattern of species indicated that 38  species were  clumped, 10 species reguler, and 13 species were at random.  The multi-plants tend to have a clumped distribution pattern, and single plant tend to have a reguler or random distribution pattern. The of association indicated that 4 species assosiation which the highest index.